Liquid Crystals: Electrically Tunable Selective Reflection of Light from Ultraviolet to Visible and Infrared by Heliconical Cholesterics (Adv. Mater. 19/2015). (13th May 2015) - Xiang, Jie; Li, Yannian; Li, Quan; Paterson, Daniel A.; Storey, John M. D.; Imrie, Corrie T.; Lavrentovich, Oleg D.
Abstract : Cholesteric liquid crystals with a new heliconical structure are demonstrated to change the color of reflected light when acted upon an alternating current electric field. As demonstrated by O. D. Lavrentovich and co‐workers on page 3014, the colors are tuned dynamically in a very broad range, from ultraviolet to visible and infrared. The electrically controlled selective reflection can be used in energy‐saving smart windows, "see‐through" displays, tunable lasers, and filters.